Analisis Risiko Keselamatan Konstruksi Pada Proyek Rehabilitasi Puskesmas Secang 2 Berdasarkan Sudut Pandang Kontraktor - Firdamarsha Benadikta; Fitri Nugraheni (Pusat Riset dan Inovasi Nasional, 2024)
The accident rate of building construction projects in Indonesia reached 9 cases out of a total of 48 cases (20%) from 2017 to 2022. Out of these, 43 cases were attributed to technical negligence, 4 cases were due to natural factors, and 1 case is currently under investigation. Given the issues related to construction accidents, this research aims to identify construction safety variables that are likely to occur and subsequently conduct a risk level analysis. The research methodology employed is a case study, followed by a risk analysis based on the Ministry of Public Works and Housing Regulation No. 10 of 2021 regarding the Guidelines for Construction Safety Management Systems. The research findings indicate that out of 34 construction safety risk variables, there were 2 hazards (5.88%) classified as high risk (B), 22 hazards (64.71%) classified as medium risk (S), and 10 hazards (29.41%) classified as low risk (K).